MotiveValidator: interactive web-based validation of ligand and residue structure in biomolecular complexes - Vařeková, Radka Svobodová; Jaiswal, Deepti; Sehnal, David; Ionescu, Crina-Maria; Geidl, Stanislav; Pravda, Lukáš; Horský, Vladimír; Wimmerová, Michaela; Koča, Jaroslav (Nucleic acids research, 2014)
Structure validation has become a major issue in the structural biology community, and an essential step is checking the ligand structure. This paper introduces MotiveValidator, a web-based application for the validation of ligands and residues in PDB or PDBx/mmCIF format files provided by the user. Specifically, MotiveValidator is able to evaluate in a straightforward manner whether the ligand or residue being studied has a correct annotation (3-letter code), i.e. if it has the same topology and stereochemistry as the model ligand or residue with this annotation. If not, MotiveValidator explicitly describes the differences. MotiveValidator offers a user-friendly, interactive and platform-independent environment for validating structures obtained by any type of experiment. The results of the validation are presented in both tabular and graphical form, facilitating their interpretation. MotiveValidator can process thousands of ligands or residues in a single validation run that takes no more than a few minutes. MotiveValidator can be used for testing single structures, or the analysis of large sets of ligands or fragments prepared for binding site analysis, docking or virtual screening. MotiveValidator is freely available via the Internet at http://ncbr.muni.cz/MotiveValidator.
Keywords: glykoproteiny; Acetylglucosamine; vazebná místa; Cholic Acid; software; Glycoproteins; Proteins; Ligands; kyselina cholová; Macromolecular Substances; proteiny; acetylglukosamin; Internet; ephrin-B3; makromolekulární látky; Ephrin-B3; Software; internet; ligandy; Binding Sites